Media effects and the criminal justice system: An experimental test of the CSI effect - Tapscott, Ryan (2011)
Across two studies, factors hypothesized to be involved in the CSI effect were examined. In study 1 (N = 245), a correlational design was used to determine relations between heavy crime drama viewers and their knowledge and expectations for scientific evidence. Heavy viewers were more knowledgeable about the criminal justice system and held greater expectations for scientific evidence than light crime drama viewers. In study 2 (N = 239), participants were randomly assigned to view four episodes of a crime drama, a medical drama, or no show and then complete measures of knowledge and expectations. Although no differences were found between conditions, results of study 2 replicated the results of study 1, showing that heavy crime drama viewers were more knowledgeable about the criminal justice system and held greater expectations for scientific evidence. Together, these studies provide support for the existence of the CSI effect. In addition, tests of mediation showed that knowledge completely mediated the relationship between crime drama viewing and expectations. Implications for future research on the CSI effect are discussed